2017
DOI: 10.1016/j.agsy.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of water-limited cropping systems in a semi-arid climate using DSSAT-CSM

Abstract: Water is the major factor limiting crop production in western Kansas due to declining groundwater levels in the Ogallala aquifer resulting from withdrawals for irrigation exceeding recharge rates coupled with erratic semi-arid rainfall. Study objectives were to assess yield and water productivity of water limited cropping systems in western Kansas using DSSAT-CSM (Decision Support System for Agrotechnology Transfer Cropping Systems Model). The cropping systems evaluated included continuous (corn, wheat, and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 34 publications
2
35
1
Order By: Relevance
“…To meet needs of a growing world population in the face of increasing climate variability, agricultural systems will be required to be more efficient in water use (Dietzel et al., 2016; Jin et al., 2017; Kang et al., 2017). There is a need to promote efficient use of water for ensuring food security in the 21st century under increased climate variability (Araya, Kisekka, Gowda, & Prasad, 2017; Kunkel et al., 2013; Wallace, 2000). The southeastern United States is one of the nation's leading commodity crop planting regions due to its intensive crop production systems (Feng, Ouyang, Adeli, Read, & Jenkins, 2018; Yang et al., 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…To meet needs of a growing world population in the face of increasing climate variability, agricultural systems will be required to be more efficient in water use (Dietzel et al., 2016; Jin et al., 2017; Kang et al., 2017). There is a need to promote efficient use of water for ensuring food security in the 21st century under increased climate variability (Araya, Kisekka, Gowda, & Prasad, 2017; Kunkel et al., 2013; Wallace, 2000). The southeastern United States is one of the nation's leading commodity crop planting regions due to its intensive crop production systems (Feng, Ouyang, Adeli, Read, & Jenkins, 2018; Yang et al., 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also indicated that winter wheat is relatively less sensitive to water stress and less water consumptive when compared to corn (Colaizzi et al 2006;Araya et al 2017a). For example, there was on an average 40% and 35% increase in grain and BM yield, respectively, by applying 190 mm irrigation under IC 5 mm/day strategy when compared to the dryland wheat.…”
Section: Et Es T Gy and Bmmentioning
confidence: 93%
“…Increased nitrogen fertilizer increased yield and BM of winter wheat when grown with irrigation. Other studies also indicated that winter wheat is relatively less sensitive to water stress and less water consumptive when compared to corn (Colaizzi et al 2006;Araya et al 2017a). For this reason, in some waterlimited areas, growing wheat and grain sorghum may contribute to water saving (Araya et al 2017a).…”
Section: Et Es T Gy and Bmmentioning
confidence: 99%
See 1 more Smart Citation
“…Crop model simulation is a widely used method to indirectly obtain crop growth status variables (e.g., leaf area index, biomass, and evapotranspiration (ET)) [5]. Many crop models, such as DSSAT-CSM, EPIC, APSIM, WOFOST and STICS etc., have been developed and refined to successfully simulate wheat growth and production under different soil moisture, fertility and salinity conditions [6][7][8][9][10]. Determination of model parameters, initial conditions and driving variables (meteorological data, soil properties, field management etc.)…”
Section: Introductionmentioning
confidence: 99%